1998
DOI: 10.1086/311314
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Mass Map of CL 0024+1654 from Strong Lensing

Abstract: We construct a high-resolution mass map of the cluster 0024ϩ1654, based on a parametric inversion z ϭ 0.39 of the associated gravitational lens. The lens creates eight well-resolved subimages of a background galaxy, seen in deep imaging with the Hubble Space Telescope. 1 Excluding mass concentrations centered on visible galaxies, more than 98% of the remaining mass is represented by a smooth concentration of dark matter centered near the brightest cluster galaxies, with a 35 kpc soft core. The asymmetry in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
323
3
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(350 citation statements)
references
References 22 publications
23
323
3
1
Order By: Relevance
“…The value of the core radius r c is somewhat uncertain. It is zero in the original NFW model, but cluster lensing studies (Tyson et al 1998;Shapiro & Iliev 2000) suggest that it may be tens of kiloparsecs in some clusters. As explained in x 3, we try two values of r c : r c ¼ 0 and r c ¼ r s =20.…”
Section: The Modelmentioning
confidence: 99%
“…The value of the core radius r c is somewhat uncertain. It is zero in the original NFW model, but cluster lensing studies (Tyson et al 1998;Shapiro & Iliev 2000) suggest that it may be tens of kiloparsecs in some clusters. As explained in x 3, we try two values of r c : r c ¼ 0 and r c ¼ r s =20.…”
Section: The Modelmentioning
confidence: 99%
“…There has been a debate about whether the inner density profile of simulated clusters really approaches an asymptote of the form / r À1 (e.g., Fukushige & Makino 1997;Moore et al 1999;Jing & Suto 2000;Power et al 2003;Fukushige et al 2004) and whether such a density cusp is consistent with observed clusters (e.g., Tyson et al 1998;Smith et al 2001;Ettori et al 2002;Kelson et al 2002;Sand et al 2002Sand et al , 2004Lewis et al 2003). Our main need is for a model other than the isothermal ellipsoid that we can apply to massive clusters and low-mass dwarf halos.…”
Section: Definitionsmentioning
confidence: 99%
“…However, a series of observations of dark matter structures on the order of < ∼ 1 Mpc (e.g., galaxy rotation curves [2,3,4], strong lensing from galaxy clusters [5], Tully-Fisher relation of spiral galaxies [6], bar stability in spirals [7,8] and deficit of low-mass subhalos in the Local Group [9]) appear to contradict the prediction of collisionless CDM simulations that dark matter halos form high-density cores, favoring shallower, lower-density dark matter halo cores.…”
Section: Introductionmentioning
confidence: 99%
“…Potential difficulties for this model may arise at cluster scales [13,5,14,15]; one way to address these would be a velocity-dependent cross section, the effect of which we will consider below.…”
Section: Introductionmentioning
confidence: 99%